通过 kahoot 媒体提高学习者的竞争力，优化对适合（Shìhé）和 合适（Héshì）内容的掌握 - Iffa Mar'atus Shohibul Birri; Wang Xin; Kencana Cherry Angger Santoso; Savira Pratista Putri; Dinie Larasati (International Journal of Chinese Interdisciplinary Studies, 2024)
摘要: 作为一门跨学科科学，教育语言学需要语言学以外的科学（包括社会学、心理学等）的支持。在外语学习者中，对比语言分析也是众所周知的。除对比语言学外，比较两种或多种语言的语言分析模式是比较语言学。对比语言学有两个方面的研究：语言学和心理学。语言方面的研究与语言对比问题有关，而心理方面的研究则涉及学习困难、如何编制学习材料以及如何提供学习材料。对比语言学分析的关键词之一，就是对比成分的存在，因为它们在母语和外语之间存在意义上的差距。在这个例子中，印尼语和汉语的成分是适合（Shìhé）和 合适（Héshì）。之所以选取这两个成分，是因为普通话中的 Shìhé 和 Héshì 与印尼语中的 Shìhé 和 Héshì 意思基本相同，都是匹配的意思。但是，印尼语和汉语的语法结构却大不相 因此，通过使用名为 Kahoot 的应用程序来提高每个学习者的竞争力，也可以提高对适合（Shìhé）和适当（Héshì）这两个组成部分的掌握程度。Kahoot 是一个基于游戏的学习平台，用于创建和玩在线互动测验。教育工作者或内容创建者可以使用该平台创建测验问题，并吸引参与者通过自己的设备（如电脑或智能手机）参与游戏。 Abstract: As an interdisciplinary science, educational linguistics requires the support of sciences other than linguistics, including sociology, psychology, etc. Comparative linguistic analysis is also well known among foreign language learners. In addition to comparative linguistics, the mode of linguistic analysis that compares two or more languages is comparative linguistics. There are two aspects of comparative linguistics: linguistics and psychology. The study of language is related to the problem of language contrast, while the study of psychology is concerned with learning difficulties, how learning materials are compiled, and how learning materials are provided. One of the key words of comparative linguistic analysis is the presence of contrasting components, since there is a difference in meaning between their mother tongue and the foreign language. In this example, the Indonesian and Chinese components are suitable (shìhé) and suitable (héshì). These two components were chosen because Shìhé and Héshì in Mandarin have basically the same meaning as Shìhé and Héshì in Indonesian, and they are both matching meanings. However, the grammatical structures of Bahasa Indonesia and Chinese are very different Therefore, by using an app called Kahoot to improve the competitiveness of each learner, it is also possible to improve the mastery of the two components of fit (Shìhé) and appropriate (Héshì). Kahoot is a game-based learning platform for creating and playing online interactive quizzes. Educators or content creators can use the platform to create quiz questions and engage participants in the game through their own devices, such as computers or smartphones